TINGKAT LITERASI EKONOMI PADA MAHASISWA PROGAM STUDI MANAJEMEN STIE INDONESIA PONTIANAK - Juliahir Barata; Yuana Yuana (Jurnal Ekonomi Integra, 2021)
The main purpose of this article's research is to describe the level of economic literacy in management students at the Indonesian College of Economic Sciences Pontianak. The research method used by the author is quantitative dexsripfi with data collection instrument in the form of questionnaires. The subject of this study was students of management study program STIE Indonesia Pontianak academic year 2019/2020 which amounted to 221 students. The data analysis uses an average calculation of the total score of questionnaire answers which is then interpreted against the table of economic literacy levels. The main findings of this study are that the level of economic literacy of students of STIE Indonesia Pontianak management study program is in the low category which is reviewed from aspects of literacy that include aspects of the ability to allocate money; financial record skills; knowledge of the benefits of savings; knowledge of debt; knowledge of insurance; decision on replacement of goods; knowledge of investments. The limitation of this study is that it is not able to identify the factors that shape economic literacy